Induced thermoluminescence dating of basalts - Derek W. G. Sears, Derek W. G. Sears (Ancient TL, 2015)
Several attempts to date basalts using natural thermoluminescence methods have failed because the phosphor, feldspar, displays anomalous fading. In the late nineteen-seventies R.D. May reported an increase in induced TL with age for Hawaiian basalts. Studies of meteorites have shown that induced TL can increase with time (or heating) due either to production of the phosphor by crystallization of glass or the diffusion of impurity quenchers out of the phosphor. The increase can be many orders of magnitude. I therefore propose that induced TL is a potential new method of thermoluminescence dating of basalts. I also suggest that it may be possible to make the method absolute, i.e. not dependent on empirical calibration, by performing the appropriate laboratory kinetic studies.